Amitermes rhizophagus Belyaeva, 1974 – a new genus and species of termites (Blattodea: Termitidae) in the fauna of Uzbekistan - Kakhramon D. Rustamov; Gulnara S. Mirzaeva; Bakhtiyor R. Kholmatov; Vakhidjon N. Akhmedov; Natalya I. Lebedeva; Zumrad A. Ganieva; Mukhabbat Kh. Khashimova (Acta Biologica Sibirica, 2024)
Turkmenistan is considered to be the habitat of termites of the genus Amitermes Silvestri, 1901 in the CIS countries. In Uzbekistan, as it turned out, they are very rare and were found for the first time for the fauna of the republic in 2024 in the south of the republic. A single species Amitermes rhizophagus Belyaeva, 1974 is registered within the genus Amitermes. Morphological features of nymphs, soldiers and workers with corresponding illustrations are described. A map of the place where the species was found is presented.